PENGATURAN TERHADAP PERSONAL GUARANTEE SEBAGAI JAMINAN PEMBERIAN KREDIT DI PT. BANK RIAU KEPRI CABANG TEMBILAHAN - Subhan; Sukamto Satoto; Dwi Suryahartati (Fakultas Hukum Universitas Islam Indragiri, 2022)
This study aims to analyze the arrangements and procedures for providing credit facilities using the Personal Guarantee as collateral and the efforts of Bank Riau Kepri Tembilahan Branch as a creditor if there are debtors who fail to fulfill their obligations (default). The type of this research is juridical empirical. The results of the research and discussion found that the Arrangements and Procedures for the Provision of Credit Facilities were carried out by taking into account the applicable laws and regulations, especially those relating to the Civil Code and the Mortgage Law, which are related toPersonal guarantee is applied to debtors whose loan value exceeds the authority of the head of the Riau Kepri branch of the Tembilahan Branch. Personal Guaranty Guarantee is carried out by taking into account the legality of the guarantor itself. Efforts made by PT. Bank Riau Kepri against creditors who fail to fulfill their obligations is carried out first with internal efforts, namely credit rescue with Credit Restructuring efforts, if internal efforts fail then external efforts are carried out by involving the Indragiri Hilir District Attorney on the basis of the MoU between Bank Riau Kepri Tembilahan Branch with the District Attorney of Indragiri Hilir, and if the efforts of deliberation and consensus by involving the prosecutor's office still fail, then Bank Riau Kepri then submits the collection to the Directorate General of State Assets/Office of State Assets and Auction Services (DJKN/KPKNL). Then the KPKNL issued a warrant for the sale of the confiscated goods. The letter is notified in writing to the debtor or guarantor as a last resort. The sale of the confiscated goods can be done by way of auction, sale not through auction or redemption.